Impacto de la implementación del sistema de gestión de inocuidad alimentaria bajo la norma ISO 22000 en Pymes de la industria de alimentos (2020)
The main objective set out in this work is to identify how and how the implementation of a food safety/safety management system in SMEs in the food industry based on ISO 22000 impacts. An analysis of this standard was made, which is responsible for food safety from the farm to consumer delivery, in addition to being certifiable for any company that is involved in the food chain (packaging, food production, additives, equipment, food service sales etc.), and that manages an APPC (Hazard Analysis and Critical Control Points) or HACCP system, which integrates with Good Manufacturing Practices.